2016
DOI: 10.1021/acssuschemeng.5b01688
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Wastewater for Production of Chelated Biodegradable Zn Micronutrient Fertilizers

Abstract: Zinc containing organic materials were synthesized using dairy wastewater and solid zinc waste derived from zinc nitrate with the goal of obtaining biodegradable, slow release, micronutrient containing fertilizers. The developed synthesis procedure involved heating at mild 55 °C temperature, followed by pH adjustment to 7, precipitation, and drying. The resulting solid materials were characterized using weight analysis, thermogravimetric analysis (TGA), X-ray diffraction (XRD), and Fourier transformed infrared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Utilization of waste streams for fertilizer production is important for advancing sustainability of industry and transition to circular economy. Recently, wastewaters from metal and dairy processing plants were used to produce zinc-containing chelated micronutrient fertilizers . Production of nitrogen-based fertilizers consumes energy, for example in the cryogenic distillation of N 2 from air, and additionally, requires hydrogen derived from fossil carbon sources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of waste streams for fertilizer production is important for advancing sustainability of industry and transition to circular economy. Recently, wastewaters from metal and dairy processing plants were used to produce zinc-containing chelated micronutrient fertilizers . Production of nitrogen-based fertilizers consumes energy, for example in the cryogenic distillation of N 2 from air, and additionally, requires hydrogen derived from fossil carbon sources.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, wastewaters from metal and dairy processing plants were used to produce zinc-containing chelated micronutrient fertilizers. 1 Production of nitrogenbased fertilizers consumes energy, for example in the cryogenic distillation of N 2 from air, and additionally, requires hydrogen derived from fossil carbon sources. Urea is one of the most widely used N-fertilizers today, but its microbial decomposition and uncontrolled leaching from soil are major hurdles that need attention.…”
Section: ■ Introductionmentioning
confidence: 99%
“…CW is composed by lactose (44-52 g.L -1 ), proteins (6-10 g.L -1 , primarily β-lactoglobulin) and lipids (4-5 g.L -1 ) 13,14 , has a high COD (50-102 gO 2 .L -1 ), and contains some hardly biodegradable proteins which require CW to be treated before being discharged 11 . Several studies about CW treatment were reported 11,15 , including its valorization through the production of: H2 20,23,25 , micronutrient fertilizers 15 , VFAs 5,19,27,29,31 or biogas production using immobilized cells 16 . Regarding this last, cell immobilization has several advantages as compared to suspended cultures since: (i)-it prevents microbes washout in continuous process by separating dilution rate and hydraulic retention time (HRT), (ii)-it allows to work at higher cell density, (iii)-it confers an advantage for the microbial consortium against adverse conditions 13 , and (iv)-it helps downstream processes as cells are retained within the support material and separated from the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a potential for a cradle-to-cradle type of regenerative engineering process design [1,2,12] where the end product of the buckwheat processing of the husk ash can be returned back to the soil to replenish the nutrients, resulting in an overall sustainable process. The sustainable use of solid waste in agriculture is of crucial importance, and prior attempts have also been made to recover the micronutrients [13].…”
Section: Introductionmentioning
confidence: 99%